Maternal childhood adversity, OXTR genotype and cognitive load impact on perceptual and behavioral responses to infant crying. (June 2019) - Hiraoka, Daiki; Nomura, Michio
Highlights: This study investigated the gene, environment and situational effects on parenting. Childhood trauma, OXTR, and cognitive load caused dysregulation of handgrip force. The three-way interaction also predicted harsh response intention to crying infant. Cognitive load decreased empathic concern only in mothers with childhood trauma. Abstract: The crying of infants elicits aversive feelings and poses a risk for child abuse. Maternal childhood maltreatment can have negative parenting ability consequences and interact with the oxytocin receptor (OXTR) single nucleotide polymorphism (rs53576) to predict maternal response to infant distress stimuli. Recent studies have highlighted the importance of individual vulnerability differences to situational cognitive load in parenting situations. The current study, in which 124 mothers participated in a standardized infant vocalization paradigm, examined three-way interaction on subjective empathy, behavior intention, and handgrip force response to a crying infant. Participants were asked to squeeze a handgrip dynamometer at maximal and half strength while memorizing a meaningless alphabet syllable as the cognitive load manipulation. Significant interactions were also observed between OXTR rs53576, childhood adversity, and cognitive load when predicting excessive force and harsh response intention on hearing a crying infant. These findings suggested that, as the G allele carriers of OXTR rs53576 appear to be susceptible to the effects of severe childhood adversity, inter- and intra-individual approaches are needed when assessing maternal responses to infant stimuli.